Cognitive impairments in former patients with work-related stress complaints – one year later. (1st November 2016) - Eskildsen, Anita; Andersen, Lars Peter; Pedersen, Anders Degn; Andersen, Johan Hviid
Abstract: Patients on sick leave due to work-related stress often present with cognitive impairments. The aim of this prospective cohort study was to examine the long-term consequences of prolonged work-related stress in terms of cognitive functioning one year after initial professional care seeking. We tested a group of patients with work-related stress with a comprehensive neuropsychological test battery at two occasions, one year apart. At both time points, we compared the performance of patients with healthy controls matched pairwise on sex, age and length of education. This paper presents the results from the one-year follow-up. When adjusting for practice effects, patients improved on measures of prospective memory and processing speed. However, patients continued to perform worse than controls on all tests, though only half of the comparisons reached statistical significance. The effect sizes of the differences between the two groups at one-year follow-up were small to medium. In conclusion, former patients with prolonged work-related stress improved, but they continued to perform worse than controls after one year. In the acute phase, the largest impairments were related to executive function and mental speed but at follow-up memory impairments also became apparent.